Exploration of Mathematics Problem Solving Processes of Junior High School Students with Different Levels of Logical Thinking Ability - Nurhalisa, Tika; Azizah, Isnainy Ibnatul; Tsania, Firdaus Qoofa Putri; Warli, Warli (Universitas Islam Negeri Raden Intan Lampung, 2022)
Problem solving is one of the most important skills for students. Meanwhile, logical thinking is the ability to solve problems by relying on mental abilities. The purpose of this research is to describe the problem solving process of students with different levels of logical thinking. This research is an exploratory qualitative research involving eighth grade students of SMP N 5 Tuban who have different levels of logical thinking as research subjects. The subjects who were interviewed were 4 students. Instruments to measure the level of logical thinking used The Group Assessment of Logical Thinking (GALT) while exploring the process of solving problems using the stages of entry, attack, and review. The results of the analysis show that students with high logical thinking skills meet the entry, attack, and review stage. Students with low logical thinking skills meet the entry stage in ‘know’ and ‘want’ aspects only, at the attack stage they only meet the try and possible aspects, and do not meet the review stage at all. Thus, it can be concluded that students with different levels of logical thinking ability have different mathematical problem solving abilities.